2017
DOI: 10.1016/j.seizure.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sertraline and 8-OH-DPAT on the PTZ_induced seizure threshold: Role of the nitrergic system

Abstract: These findings support the anticonvulsant effect of SSRIs and selective 5HT receptors, although serotonin receptors other than 5HT subtype may be involved and also it is probable that some anticonvulsant effects of the sertraline and 8-OH-DPAT are through the modulation of nitrergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In line with previous reports, the current study identified marked decreases in the levels of 5-HT and its metabolite (5-HIAA), DA, and NE and reduced AChE activity in PTZ-injected rats, which was accompanied by apparent increases in the DOPAC and HVA levels. Deficiencies in the levels of biogenic amines have been demonstrated to trigger seizure susceptibility and the development of behavioral deficits and neuropathological deficits in clinical and experimental studies [44][45][46]. Earlier reports showed a disturbance in the synthesis, release, and reuptake of monoamines following the initiation of epileptic seizures [47].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous reports, the current study identified marked decreases in the levels of 5-HT and its metabolite (5-HIAA), DA, and NE and reduced AChE activity in PTZ-injected rats, which was accompanied by apparent increases in the DOPAC and HVA levels. Deficiencies in the levels of biogenic amines have been demonstrated to trigger seizure susceptibility and the development of behavioral deficits and neuropathological deficits in clinical and experimental studies [44][45][46]. Earlier reports showed a disturbance in the synthesis, release, and reuptake of monoamines following the initiation of epileptic seizures [47].…”
Section: Discussionmentioning
confidence: 99%
“…In rat studies, sertraline provided reductions in the severity of generalized tonic-clonic seizures as well as secondarily generalized seizures [ 261 ]. Sertraline prevented tonic-clonic seizures and the epileptiform EEG activity induced by pro-convulsive (4-AP and PTZ) agents [ 262 , 263 ]; an effect comparable to the clinically established ASM carbamazepine [ 264 , 265 ]. Vortioxetine, a new AD approved for the treatment of the major depressive disorder (MDD), is a multimodal and selective serotonin reuptake inhibitor (SSRI) antidepressant that combines 5-HT 1A receptor agonism with serotonin transporter (SERT) inhibition [ 266 ].…”
Section: Current Treatment Of Depression In Epilepsymentioning
confidence: 99%
“…Depleting 5-HT increases seizure severity, and sertraline or optogenetic stimulation of raphe nuclei dose-dependently prevents respiratory arrest induced by audiogenic seizures or proconvulsants, respectively, in seizure-prone mice. , SSRIs, however, indiscriminately and indirectly activate all 5-HT receptors (5-HTRs); targeting individual 5-HTRs is a more precise strategy for effecting therapeutic outcomes. With few exceptions, many studies show that activating 5-HT 1A Rs, either systemically or via direct injections into the hippocampus, attenuates seizures induced by both GABA antagonists and glutamate agonists in wild-type animals. Also, 5-HT 7 R antagonism appears to prevent audiogenic seizures in mouse models . Two recent, though small, clinical trials reported that the selective 5-HT 2C R agonist lorcaserin (Belviq) effectively treats seizures in childhood-onset epilepsies. , These data provide compelling evidence that distinct 5-HTRs can modulate critical inhibitory and excitatory neural circuitry that translates behaviorally.…”
Section: Introductionmentioning
confidence: 99%